Face recognition using eigenfaces and neural networks - Mohamed Rizon; Muhammad Firdaus, Hashim; Puteh, Saad; Sazali, Yaacob, Prof. Dr.; Mohd Rozailan, Mamat; Ali Yeon, Md Shakaff, Prof. Dr.; Abdul Rahman, Saad; Hazri, Desa, Dr.; Karthigayan, M. (Science Publications, 2011)
Link to publisher's homepage at http://www.scipub.org/